2017
DOI: 10.1038/srep44353
|View full text |Cite
|
Sign up to set email alerts
|

Taishan Pinus massoniana pollen polysaccharide inhibits subgroup J avian leucosis virus infection by directly blocking virus infection and improving immunity

Abstract: Subgroup J avian leucosis virus (ALV-J) generally causes neoplastic diseases, immunosuppression and subsequently increases susceptibility to secondary infection in birds. The spread of ALV-J mainly depends on congenital infection and horizontal contact. Although ALV-J infection causes enormous losses yearly in the poultry industry worldwide, effective measures to control ALV-J remain lacking. In this study, we demonstrated that Taishan Pinus massoniana pollen polysaccharide (TPPPS), a natural polysaccharide ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 40 publications
3
10
0
1
Order By: Relevance
“…All of the above results showed that LGFP-3 could inhibit the ALV-J adsorption and reduce the infection probability of virus. Similar results were obtained by Yu et al, who discovered that the polysaccahrides from Taishan Pinus massoniana pollen could directly coat to the virus envelope protein, which would bind to the cell surface receptor, thereby affecting the virus adsorption [ 1 ]. Because LGFP-3 had no impact on ALV-J when applied before adsorption (BA), we speculated that our samples could not bind to the cell membrane, and the possible way was to interact with the virus envelope protein just like the polysaccahrides from Taishan Pinus massoniana pollen.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…All of the above results showed that LGFP-3 could inhibit the ALV-J adsorption and reduce the infection probability of virus. Similar results were obtained by Yu et al, who discovered that the polysaccahrides from Taishan Pinus massoniana pollen could directly coat to the virus envelope protein, which would bind to the cell surface receptor, thereby affecting the virus adsorption [ 1 ]. Because LGFP-3 had no impact on ALV-J when applied before adsorption (BA), we speculated that our samples could not bind to the cell membrane, and the possible way was to interact with the virus envelope protein just like the polysaccahrides from Taishan Pinus massoniana pollen.…”
Section: Discussionsupporting
confidence: 78%
“…Different plant polysaccharides exerted various antiviral characteristics [ 1 , 27 , 28 ]. In order to explore the action phase of the samples, LGFP-3 was assayed following different conditions, as indicated in Section 4.7.2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the lower SI found in these cells compared with that found in MA104 cells, LJ04 effectively inhibited EV71 proliferation in HM1900 cells, and the expression of EV71 VP1 was inhibited by this polysaccharide in both MA104 and HM1900 cells. Antiviral mechanisms are complex systems, and the potential antiviral mechanisms that have been previously identified in vitro include the following: (i) a drug can directly interfere the binding between cells and viral particles, [40][41][42] (ii) a drug can regulate antivirus-related signaling pathways and cytokines, [43][44][45][46] and (iii) a drug can directly suppress the activity of nonstructural proteins or the proliferation of viruses. [47][48][49] This study found that LJ04 is mainly composed of fucose, galactose, and mannose and can be considered a typical acidic polysaccharide, specifically a unique watersoluble polysaccharide with negative charge.…”
Section: Discussionmentioning
confidence: 99%
“…Natural plant polysaccharides, which are polymeric carbohydrate molecules composed of long chains of monosaccharide units, have different biological activities, including anti-inflammatory activities, immunological regulation, oxidation resistance, and antiviral activities. Numerous studies have reported the inhibitory effects of plant polysaccharides, such as brown algal polysaccharides, Auricularia auricula polysaccharides, Pinus massoniana pollen polysaccharides, and Acanthopanax sciadophylloides polysaccharides, on the replication of human and animal viruses ( Queiroz et al, 2008 ; Nguyen et al, 2012 ; Lee et al, 2015 ; Yu et al, 2017 ). In our study, we focused on Aloe vera , which is a perennial Liliaceae evergreen herbaceous plant widely grown in the tropical and subtropical regions.…”
Section: Introductionmentioning
confidence: 99%